Scientific debate on human migration: ethics, challenges, and solutions - Yen, Peter Tsung-Wen; Cheong, Siew Ann (Frontiers in Physics, 2023)
In recent years, we witnessed increasing numbers of migrants worldwide owing to famine, poverty, regional conflicts, etc. Efforts by the United Nations and various organizations to help these migrants are hampered by rising anti-migrant sentiments and xenophobic rhetoric in many parts of the world. To arrive at win-win solutions that benefit both natives and migrants, we must discuss the migration problem objectively and scientifically. To do this, we must first resolve the paradox in our understanding of human migration (widely touted as good) vis-a-vis biological invasion (generally regarded as bad). Suspecting that the two similar phenomena are more complex than we think, we reviewed and synthesized the disjoint literatures on human migration and biological invasion in recent times, and that on the human diaspora and human-aided dispersal of plants and animals in our pre-historic past. We then developed models of niche-niche interactions to simulate isolated ecosystems and communities, as well as those experiencing invasions from non-native populations. In this paper, we simulated four invasion mechanisms on a star network: the direct introduction of a non-native population into existing periphery or core niches, or the non-native population first creating its own niche, which is thereafter attached to the periphery or core of the community. We found that periphery invasions can fail, i.e., the non-native population eventually disappears. When periphery invasion is successful, we found that there is little or no harm to the ecosystem or community. On the other hand, core invasion is always catastrophic, where the non-native population establishes itself at the expense of most or all of the native populations. For niche attachments, whether to the periphery or to the core, we found native and non-native populations coexisting in the end, frequently with increased diversities. Our results provide promising new insights and theoretical grounds for policy makers to put ethical discussions on immigration issues on firm scientific foundations, and to ultimately discover win-win solutions for natives and migrants. The theoretical framework outlined in this paper can also be applied to the problem of introducing non-native biological species for economic gains, at acceptable ecological costs.